Utilization of Asteraceae family as medicinal plant by local community of hutan pinus Jantho nature reserve, Aceh Besar - LIZA FADHILLAH; SAIDA RASNOVI; ZAIRIN THOMY (Universitas Syiah Kuala, 2021)
The use of medicinal plants by local communities is an ethnobotany study that links the culture of the community with the resources of plants that are around it. A study on the utilization of medicinal plants in the Hutan Pinus Jantho Nature Reserve was conducted with the aim of obtaining information about the types of medicinal plants used by local communities around Hutan Pinus Jantho Nature Reserve. This study applies the Participatory Rural Appraisal (PRA) method for interviews conducted by Purposive Sampling. The parameters measured are; parts of medicinal plants used, method of processing, method of use, and location of the collection. According to interview, it found about 10 species of Asteraceae those have medical potential, 3 of them already use by the local community of CAHPJ, these are Blumea balsamifera L., Chromolaena odorata L., and Tagetes erecta L., these species could cure the wound, heal the cold, fever, stomachache and other diseases.